Study on Alfalfa Water Use Efficiency and Optimal Irrigation Strategy in Agro-Pastoral Ecotone, Northwestern China - Xiangyang Miao; Guoshuai Wang; Bing Xu; Ruiping Li; Delong Tian; Jie Ren; Zekun Li; Ting Fan; Zisen Zhang; Qiyu Xu (Agronomy)
Agro-pastoral ecotone is an important livestock production area in the north of China, and alfalfa is the main pasture crop in this area. Aiming to address the issues of groundwater overexploitation in the area with water demand, we assessed the consumption pattern, irrigation scheduling, and water usage efficiency of alfalfa under subsurface drip irrigation. Alfalfa was used as the research object in this study. A DSSAT model was used to simulate the soil moisture, yield, and other alfalfa grow characteristics during a two-year in situ observation study and provide information on the best irrigation techniques and the water-use efficiency of alfalfa in the agro-pastoral ecotone of Northwestern China. The results showed that the ARE, nRMSE, and R2 values of the alfalfa soil water content, leaf area index, and yield varied between 3.82% and 5.57%, 4.81% and 8.06%, and 0.86 and 0.93, respectively, the accuracy of the calibrated and validated parameters were acceptable, and the model could be applied to this study. The water consumption of alfalfa ranged from 395.6 mm to 421.8 mm during the whole year, and the critical water consumption period was the branching stage and the bud stage. During the branching stage and the bud stage, water consumption was 30–31% and 31–33% of the total water consumption, and the water consumption intensity averaged 2.97–3.04 mm/d and 4.23–4.97 mm/d. The variations of WUE and IWUE were 11.74–14.39 kg·m−3 and 7.12–9.31 kg·m−3. Irrigation increased the water productivity of rain-fed alfalfa by 49.48–64.70% and increased the yield of alfalfa by 17.87–34.72%. With the highest yield as the goal, the recommended irrigation volumes for normal and dry flow years were 200 mm and 240 mm; with the goal of the highest utilization of groundwater resources, the recommended irrigation volumes for normal and dry flow years were 160 mm and 192 mm. The results of this study are expected to provide scientific and technological support for the rational utilization of groundwater and the scientific improvement of alfalfa yields in the agro-pastoral ecotone of Northwestern China.